Influence of Lysine Nε-Trimethylation and Lipid Composition on the Membrane Activity of the Cecropin A-Melittin Hybrid Peptide CA(1-7)M(2-9) - Vitor Teixeira (2010)
Although many studies have pointed out the promising role of antimicrobial peptides (AMPs) as therapeutical agents, their translation into clinical research is being slow due to the limitations intrinsic to their peptide nature. A number of structural modifications to overcome this problem have been proposed, leading to enhanced AMP biological lifetimes and therapeutic index. In this work, the interaction between liposomes of different lipidic composition and a set of lysine Nε-trimethylated analogs of the cecropin A and melittin hybrid peptide, CA(1-7)M(2-9) [H-KWKLFKKIGAVLKVL-amide], was studied by differential scanning calorimetry (DSC) and fluorescence spectroscopy. The study was carried out using membrane models for mammalian erythrocytes (zwitterionic lipids) and for bacteria (mixture of zwitterionic and negatively charged lipids). The results show that trimethylated peptides interact strongly with negatively charged (bacterial cell model) but not with zwitterionic (erythrocyte model) liposomes. These results are in agreement with the reduction of cytotoxicity and ensuing improvement in therapeutic index vs parental CA(1-7)M(2-9) found in a related study. Moreover, the modified peptides act differently depending on the model membrane used, providing further evidence that the lipid membrane composition has important implications on AMP membrane activity.